Cyclic Soft Groups and Their Applications on Groups - Hacı Aktaş; Şerif Özlü (The Scientific World Journal)
In crisp environment the notions of order of group and cyclic group are well known due to many applications. In this paper, we introduce order of the soft groups, power of the soft sets, power of the soft groups, and cyclic soft group on a group. We also investigate the relationship between cyclic soft groups and classical groups.